Verktygsrelaterad flexibilitet som undervisningskompetens: En fallstudie av tre multiinstrumentala musiklärare - Frostenson Lööv, Cecilia Charlotta; Huovinen, Erkki (Educare, 2021)
In the current debate concerning the Swedish Schools of Music and Performing Arts (SMPAs) the concept of flexibility is frequently used. Here it mostly describes the necessity to take students’ requests and needs into account in teacher education and the institutions’ ability to adapt to changing demands for artistic activities among children and adolescents. In contrast to this view, this study examines flexibility as a central competency of the teaching profession and particularly in a curriculum-free environment such as the SMPAs. Resting on the assumption that teachers with a large toolkit have a certain advantage in practising flexibility, the study is based on interviews with three multi-instrumentalists, all of them experienced music teachers in SMPAs. The analysis suggests three forms of flexibility that are related to the teachers’ use of instrumental tools, each of them emerging in particular kinds of teaching activities: problem-solving flexibility in instrument-related counseling, method flexibility in ensemble leadership, and role flexibility in group music-making. The findings are discussed in relation to ideals of teacher specialization and versatility, and the notion of tool-based flexibility is distinguished from improvisation as a teaching skill.